2003
DOI: 10.1016/s0042-6822(02)00025-9
|View full text |Cite
|
Sign up to set email alerts
|

The L1 major capsid protein of human papillomavirus type 11 interacts with kap β2 and kap β3 nuclear import receptors

Abstract: We have previously shown that the L1 major capsid protein of low-risk HPV11 binds to the Kap alpha2 adapter and enters the nucleus via a Kap alpha2beta1-mediated pathway. In this study, we discovered that HPV11 L1 capsomeres bind to Kap beta2 import receptor, known to mediate nuclear import of hnRNP A1 via interaction with its nuclear localization signal termed M9. Significantly, binding of HPV11 L1 capsomeres to Kap beta2 inhibited the nuclear import of Kap beta2, and its specific M9-containing cargo. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…1 and 2). Utilization of the ␣/␤ transport pathway by E1 is consistent with previous observations that several other papillomavirus proteins, including L1 (HPV11, HPV16, and HPV45), L2 (HPV16), and E6 (HPV16), also enter the nucleus via the importin ␣1/␤1 pathway (11,32,39,(41)(42)(43). In addition, we found that HPV11 and HPV16 E2 proteins, which both contain a well-characterized NLS (4,55,67), also displayed in vitro binding to importins ␣3 and ␣5 (unpublished data).…”
Section: Discussionsupporting
confidence: 91%
“…1 and 2). Utilization of the ␣/␤ transport pathway by E1 is consistent with previous observations that several other papillomavirus proteins, including L1 (HPV11, HPV16, and HPV45), L2 (HPV16), and E6 (HPV16), also enter the nucleus via the importin ␣1/␤1 pathway (11,32,39,(41)(42)(43). In addition, we found that HPV11 and HPV16 E2 proteins, which both contain a well-characterized NLS (4,55,67), also displayed in vitro binding to importins ␣3 and ␣5 (unpublished data).…”
Section: Discussionsupporting
confidence: 91%
“…The restricted localization of importin beta 3 protein to the elongating spermatids in the adult testis supports this concept, conceivably representing a mechanism for effecting translational regulation in postmeiotic male germ cells. Importin beta 3 (also named Ran BP5) has been implicated in nuclear transport of ribosomal proteins [30,31] as well as of certain transcription factors and viral proteins [32,33]. The abundance of importin beta family members appears to provide some degree of functional redundancy, as illustrated by the ability of importins beta 1, 2, 3, and 7 all to mediate nuclear transport of the ribosomal protein L23a, at least in vitro [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RanBP5 has been shown to interact with proteins from a range of viruses (Arnold et al, 2006;Chung et al, 2000;Darshan et al, 2004;Deng et al, 2006;Klucevsek et al, 2006;Krawczyk et al, 2008;Nelson et al, 2003). In influenza A virus, RanBP5 could be displaced from PB1 or the PB1 : PA dimer by the addition of non-hydrolysable RanGTP in vitro, and depletion of RanBP5 reduced the nuclear accumulation of PB1 and of PB1 : PA.…”
Section: Introductionmentioning
confidence: 99%